Need Analysis of English Course Materials For The First Grade of Food Crops And Horticulture Students of SMKN 4 Sidrap - Yessicka Noviasmy (IAIN Parepare, 2022)
The main objectives of this research are to find out the student’s needs in learning English as a general course and also the target language needs for materials and to design an appropriate syllabus on the basis of agricultural student’s needs especially in food crops and horticulture. In order to achieve these objectives, a need analysis of the students was carried out in advance. The research method employed descriptive research. The research was carried out by distributing questionnaires to collect the relevant data. The data collected were tabulated and analyzed using both descriptive and quantitatif methods. The population of this reserach was all the first grade of food crops and horticulture students consisted 25 students and one English Instructor and one Vocational Teacher. The result of the research indicated that learning needs questionnaires given on speaking and listening activities. Based on the questionnaires showed that learning needs of perceptions of sudents skills regarding the importance of item referring to speaking skill were 94,4% ,the subskills highest importance is listening 93,6%, and other were writing 92,8% and reading 90,4%. Target language needs as perception of students regarding the importance of students reffering to speaking skils were 95,2%, and listening as the next skill with 94,4%. Reading and writing skills have the same range of 93,6% according to perception of respodents. Based in this fact, a syllabus that meets the students expectation specially related to teaching material, teaching method and leraning strategies is to be designed that using in curriculum 2013.